PENGARUH KNOWLEDGE SHARING DAN KEPERCAYAAN TERHADAP KINERJA KARYAWAN PT. TUNAS DWIPA MATRA KEPAHIANG - Praningrum, Praningrum; Febrianto, Febrianto (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2019)
The purpose of this study is to analyze the effect of knowledge sharing and trust on employee performance at PT Tunas Dwipa Matra Kepahiang, Bengkulu Province. This study used a survey approach by distributing questionnaires to the research sample that consisted of 40 respondents who were the staff and managers at PT Tunas Dwipa Matra Kepahiang. Data were analyzed by multiple linear regression analysis using SPSS program. Results showed that knowledge sharing and trust had a positive and significant effect on employee performance at PT Tunas Dwipa Matra Kepahiang. Thus, the company could improve the knowledge sharing activities related to the work procedures and clear tasks division among its employees based on mutual trust to achieve the best performance.